Surgery in Liver Diseases: Perioperative Evaluation & Management - Ulfa Kholili; Denada Aisyah Syalini (The Indonesian Society for Digestive Endoscopy, 2016)
Many patients with liver disease would have to undergo surgery. Surgery and anesthesia in patients with liver disease are associated with extremely high perioperative complications and mortality. Identification of the type of liver disease, stratification of risk factors, and management of preoperative, intraoperative, and postoperative complications are essential to reduce the morbidity and mortality. Surgical risk is increased in patients with liver cirrhosis. Child turchote pugh (CTP) and the model for end stage liver disease (MELD) are two scoring systems which are often used nowadays to stratify risk factors in patients with liver cirrhosis who will undergo surgery. Elective surgery is well tolerated in cirrhosis patients with CTP class A and permissible in patient with CTP class B with preoperative preparation, except for extensive liver resection surgery and cardiac surgery. Elective surgery is contraindicated in patients with CTP class C, acute viral hepatitis, alcoholic hepatitis, fulminant liver failure, and liver disease with severe extrahepatic complication such as hypoxemia, cardiomyopathy, and acute renal failure. Intensive monitoring in the postoperative period and early intervention of complications are also essential to reduce the morbidity and mortality.